Characterization of oqxAB in Escherichia coli Isolates from Animals, Retail Meat, and Human Patients in Guangzhou, China - Wang, Jing; Zhi, Chan-Ping; Chen, Xiao-Jie; Guo, Ze-Wen; Liu, Wu-Ling; Luo, Juan; Huang, Xin-Yi; Zeng, Li; Huang, Jia-Wei; Xia, Ying-Bi; Yi, Meng-Ying; Huang, Teng; et al. (Frontiers in Microbiology, 2017)
The purpose of this study was to investigate the prevalence and genetic elements of oqxAB among Escherichia coli isolates from animals, retail meat, and humans (patients with infection or colonization) in Guangzhou, China. A total of 1,354 E. coli isolates were screened for oqxAB by PCR. Fifty oqxAB-positive isolates were further characterized by pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), S1-PFGE, genetic environment analysis, plasmid replicon typing, and plasmid sequencing. oqxAB was detected in 172 (33.79%), 60 (17.34%), and 90 (18.07%) E. coli isolates from animal, food, and human, respectively. High clonal diversity was observed among oqxAB-positive isolates. In 21 oqxAB-containing transformants, oqxAB was flanked by two IS26 elements in the same orientation, formed a composite transposon Tn6010 in 19 transformants, and was located on plasmids (33.3~500 kb) belonging to IncN1-F33:A-:B- (n = 3), IncHI2/ST3 (n = 3), F-:A18:B- (n = 2), F-:A-:B54 (n = 2), or others. Additionally, oqxAB was co-located with multiple resistance genes on the same plasmid, such as aac(6’)-Ib-cr and/or qnrS, which were identified in two F-:A18:B- plasmids from pigs, and blaCTX-M-55, rmtB, fosA3, and floR, which were detected in two N1-F33:A-:B- plasmids from patients. The two IncHI2/ST3 oqxAB-bearing plasmids, pHNLDF400 and pHNYJC8, which were isolated from human patient and chicken meat, respectively, contained a typical IncHI2-type backbone, and were similar to each other with 2-bp difference, and also showed 99% identity to the Salmonella Typhimurium oqxAB-carrying plasmids pHXY0908 (chicken) and pHK0653 (human patient). Horizontal transfer mediated by mobile elements may be the primary mechanism underlying oqxAB spread in E. coli isolates obtained from various sources in Guangzhou, China. The transmission of identical oqxAB-carrying IncHI2 plasmids between food products and humans might pose a serious threat to public health.